Model Pengelolaan Limbah Usaha Tahu Ditinjau Dari Konsep Maqasid Syariah (Studi Kasus di Kelurahan Sari Rejo) - Pratama, M. Luthfi Arif; Harahap, Muhammad Ikhsan; Dharma, Budi (ITB AAS INDONESIA Surakarta, 2024)
Waste management is closely associated with industry. Poor waste management practices can negatively affect the environment, contaminate nearby areas, and pose health risks to people. In light of these issues, this study focuses on 1) How to process the use of solid waste and liquid waste so that it can be reused or consumed again.2 ) What is Maslahah Mursale's analysis of the value of Hifdzu an-Nafs, Hifdzu al-Mal, Hifdzu al-Bi'ah in handling trash from the tofu business. This study employs a qualitative methodology as a case study. This study's main sources of data include observations, conversations with tofu factory managers, local communities and consumers who buy tofu waste and descriptive analysis. Reviewed with secondary data in the form of general conditions of the research location as well as journals, previous research and matters related to research. Techniques for qualitative descriptive data analysis are used in this study. The findings of this study are 1) in the management of liquid waste from the tofu industry into Nata de soya which has economic value. 2) in the management of liquid waste in the tofu industry in Kel. Sari Rejo, the researchers linked several efforts that were or were not in accordance with maqasid syari'ah. There are three points, namely hifdzuh Hifdzu al-mal (care for assets), hifdzu al bi'ah (care for the environment), and an-nafs (care for the soul).